Helicene Chemistry From Synthesis to Applications - Chen, Chuan-Feng; Shen, Yun (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book systematically reviews recent advances in the synthetic methods and applications of helicenes. The first part of this book introduces the nomenclature and structural features of helicenes. The second part reviews several classic and useful methods as well as recently-developed approaches for the preparation and functionalization of helicenes, including photocyclization and Diels-Alder reactions, which are two important breakthroughs in the syntheses of helicenes. In the last part, the applications of helicenes in asymmetric syntheses, molecular machines, molecular recognition, self-assembly and other fields are discussed. This book provides a useful reference source for researchers and graduate students working not only in the area of helicene chemistry, but also in other research areas including materials science, supramolecular chemistry, coordination chemistry, and physical organic chemistry. Chuan-Feng Chen is a Professor at the Institute of Chemistry,Chinese Academy of Sciences, China.